GAMBARAN KARAKTERISTIK GARAM BERIODIUM, PENYIMPANAN, TEMPAT MEMBELI GARAM DAN JUMLAH KONSUMSI PADA KELUARGA MISKIN DI KECAMATAN KALIDERES, JAKARTA BARAT - Liana Saputri; Moesijanti Soekatri (PERSATUAN AHLI GIZI INDONESIA, 2006)
Iodine Deficiency Disorder is one of Health problem that influences directly to the life expectancy and the quality of Human being as well as delaying the goal of National Development. The survey of iodized salt consumption reported by BPS (Central Statistics Bureau) in 2003 shows that in West Jakarta the number of households who consumed an adequate iodine salt( = 30 ppm) was 66.32%. This figure is highest compared to the other four Districts in Jakarta and this becomes more important to prevent the deficiency of iodine such as cretinism and the swallowed neck. The aim of the study is gain the information related to the usage of salt, storage, place of buying and the consumption of iodized salt among poor families lived in sub district Kalideres, West Jakarta in 2006. This study is cross sectional. The sampel of the study is poor household lived in subdistrict Kalideres, West Jakarta involving 60 poor households who received JPBSK (social safety net in health) taken from Puskesmas Kalideres. The number of samples was based on random sampling formula. The study site was taken based on Multistage random sampling then sample was chosen through systematic random sampling. The analysis of tables both univariate and bivariate are used to interpret the results. The result shows that most of poor households bought the salt in small shop closed to their houses. The brand names of iodized salt used by almost all poor households are Segitiga Emas, with very fine grade, and generally it was stored in closed container with the average price of Rp.500,- per pack . It was also found that in the households level, the salt was stored in a color-plastic-container and lived it opened in cupboard or on the table, far away from heat. The salt was kept with average storage of 5.6 +0.7 hari. The interesting part of the study is that the salt commonly consumed by most poor households still contained iodine with adequate amount reflected by the existing of purple color using iodine test. The consumption level of the salt was 9.6+0.5 gram per person/d.Key words: Iodized salt, characteristic of iodine salt